CLINICALLY RELEVANT MINOR HISTOCOMPATIBILITY ANTIGENS FOR RUSSIAN PATIENTS UNDERGOING HEMATOPOIETIC STEM CELL TRANSPLANTATION - D. S. Romaniuk; A. A. Khmelevskaya; A. M. Postovskaya; D. B. Malko; E. P. Kuzminova; E. G. Khamaganova; G. A. Efimov (Медицинская иммунология, 2019)
Hematopoietic stem cell transplantation (HSCT) from healthy donors is used for blood cancer treatment. Alloreactive graft-versus-host disease (GvHD) is one of the post-transplant detrimental side effects, and the main reason for GVHD after HSCT fully matched for human leukocyte peptide antigens (HLA) presented by HLA molecules on cell surface. These polymorphic peptides, minor histocompatibility antigens (MiHA), arise from any genes, including those expressed at hematopoietic tissues. The latter may lead to the s.c. graft-versus-leukemia effect (GvL), thus preventing relapse of a malignancy. A*02:01 is one of the most frequent HLA alleles for European part of Russia. We assessed frequencies for 20 MiHA-encoded genetic polymorphisms, presented via A*02:01 allele, for plausible bone marrow donors, or hematopoietic stem cells (HSC) from the Donor Registry at Russian National Research Center for Hematology, we have also determined a number of immunogenic mismatches for these 20 MiHA in real donor – recipient pairs. A total of 608 potential donors, 90 donors and 92 recipients were genotyped. Using public data, we have shown that frequencies for MiHA coding genes are most close to appropriate frequencies among the European population. We have calculated probability of MiHA-specific alloimmune response after HSCT: there are chances of 33 and 75% for three or more immunogenic mismatches (IM) for related and unrelated HSCTs, respectively. Real frequencies for immune mismatch in 20 related and 20 unrelated donor – recipient pairs are in accordance with estimated theoretical probabilities. As based on the calculated frequencies, we suggest the LB-NDC80- 1P/A, LB-CCL4- 1T, and HA-1 MiHA to be the most promising minor antigens for targeted cell therapies of hematopoietic tissue malignancies. The data obtained could be used for planning allo-HSCTs in Russian patients.